2018
DOI: 10.1002/chem.201705714
|View full text |Cite
|
Sign up to set email alerts
|

A Unique (3+2) Annulation Reaction between Meldrum's Acid and Nitrones: Mechanistic Insight by ESI‐IMS‐MS and DFT Studies

Abstract: The fragile intermediates of the domino process leading to an isoxazolidin-5-one, triggered by unique reactivity between Meldrum's acid and an N-benzyl nitrone in the presence of a Brønsted base, were determined thanks to the softness and accuracy of electrospray ionization mass spectrometry coupled to ion mobility spectrometry (ESI-IMS-MS). The combined DFT study shed light on the overall organocatalytic sequence that starts with a stepwise (3+2) annulation reaction that is followed by a decarboxylative proto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 45 publications
1
7
0
Order By: Relevance
“…In this context, we propose that the intramolecular attack of the phenol moiety to the electrophilic MA platform 1 a is promoted by the Brønsted base 3 g (Scheme ), and the facile fragmentation‐decarboxylation process via D to lead to the rather stable tetrasubstituted enolate intermediate A (Scheme ) . Then, the bifunctional protonated‐cupreine organocatalyst 3 g‐H would deliver the proton to the rear‐face of the enolate A to give 2 a , through a hydrogen‐bonding manifold by means of the hydroxyl‐quinoline part in the Transition State (see SI for TS‐proposal discussion)…”
Section: Methodsmentioning
confidence: 99%
“…In this context, we propose that the intramolecular attack of the phenol moiety to the electrophilic MA platform 1 a is promoted by the Brønsted base 3 g (Scheme ), and the facile fragmentation‐decarboxylation process via D to lead to the rather stable tetrasubstituted enolate intermediate A (Scheme ) . Then, the bifunctional protonated‐cupreine organocatalyst 3 g‐H would deliver the proton to the rear‐face of the enolate A to give 2 a , through a hydrogen‐bonding manifold by means of the hydroxyl‐quinoline part in the Transition State (see SI for TS‐proposal discussion)…”
Section: Methodsmentioning
confidence: 99%
“…Getting experimental evidence of intermediates involved in a complex organocatalyzed MCR is not a trivial task, especially with labile Meldrum’s acid derivatives . By means of soft electrospray ionization mass spectrometry (ESI-MS), key intermediates were sought at various time intervals.…”
Section: Resultsmentioning
confidence: 99%
“…Getting experimental evidence of intermediates involved in a complex organocatalyzed MCR is not a trivial task, especially with labile Meldrum’s acid derivatives . By means of soft electrospray ionization mass spectrometry (ESI-MS), key intermediates were sought at various time intervals. We reasoned that the pyridyl moiety onto aldehyde 3g would afford an ideal probe to detect ions (protonated intermediates) in positive mode.…”
Section: Resultsmentioning
confidence: 99%
“…Moon, Hawker, and co‐workers reported that a piperidinyl group on a 2‐carbon tether promotes ketene formation presumably through an intramolecular interaction between the tertiary amine and the carbonyl carbon, which promotes the loss of acetone . In another study, Tognetti, Loutelier‐Bourhis, Brière, and co‐workers reported that a tertiary amine can work as an organocatalyst, allowing the addition of the oxygen atom to the carbonyl group with a moderate activation barrier upon proton transfer from a hydroxylamine moiety to the tertiary amine . Moon, Hawker, and co‐workers also reported that an intermolecular hydrogen bond between a Brønsted acidic hydroxy group and the dioxinone oxygen effectively promotes the loss of carbon dioxide .…”
Section: Methodsmentioning
confidence: 99%
“…[19] In another study,T ognetti, Loutelier-Bourhis, Brire, and co-workersr eported that a tertiarya mine can work as an organocatalyst, allowing the addition of the oxygen atom to the carbonyl group with am oderate activation barrier upon protont ransfer from ah ydroxylamine moiety to the tertiary amine. [20] Moon, Hawker,a nd coworkers also reported that an intermolecular hydrogen bond between aB rønsted acidic hydroxy group and the dioxinone oxygen effectively promotes the loss of carbond ioxide. [19] Based on these reported precedents, we envisioned that Meldrum's acid derivative 3,w hich bears aL ewis base (tertiary amine), could undergo decomposition to form lactone 4 under appropriate reactionconditions (Scheme 1c).…”
mentioning
confidence: 95%